Aging, Savings, and Pensions in the Group of Seven Countries : 1980-2025. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
In the next 30-40 years, past changes in fertility and mortality will lead to a significant increase in the share of the elderly. This study suggests that these demographic trends may lead to a decline in the G-7 private savings rate after 2000, compounding the impact of social expenditure pressures on the government's deficit. Moreover, public pensions may decline as a share of the consumption needs of the elderly, leading to financial pressures to reduce their consumption. The reduced burden of child support on the working population will not offset the increased burden of societal support for the elderly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet